2000
DOI: 10.4065/75.4.414
|View full text |Cite
|
Sign up to set email alerts
|

Position-Dependent Ventricular Tachycardia Related to a Peripherally Inserted Central Catheter

Abstract: Recently, peripherally inserted central venous catheters (PICCs) have been widely used for venous access. Advantages of a PICC over centrally inserted central catheters include the virtual elimination of the risk of pneumothorax, hemothorax, and arterial puncture, along with a reduced risk of bleeding. However, the PICC has associated risks. We present 2 cases of body position-dependent ventricular tachycardia related to PICCs. These events occurred in patients with no prior history of cardiac arrhythmia and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…A number of cases have documented peripherally-inserted central catheters (PICC lines) causing positional arrhythmias. We found four cases of ventricular tachycardia (two in adults, two in paediatric patients) and one case of atrial fibrillation caused by positional changes in patients with PICC lines [8][9][10]. It should be noted that arm position has been shown to have a significant effect on catheter tip position with PICC lines and while the same association between arm and catheter tip position does not exist with TIVASs, these cases underscore the potential for central venous access systems to displace internally and cause rhythm disturbances.…”
Section: Discussionmentioning
confidence: 85%
“…A number of cases have documented peripherally-inserted central catheters (PICC lines) causing positional arrhythmias. We found four cases of ventricular tachycardia (two in adults, two in paediatric patients) and one case of atrial fibrillation caused by positional changes in patients with PICC lines [8][9][10]. It should be noted that arm position has been shown to have a significant effect on catheter tip position with PICC lines and while the same association between arm and catheter tip position does not exist with TIVASs, these cases underscore the potential for central venous access systems to displace internally and cause rhythm disturbances.…”
Section: Discussionmentioning
confidence: 85%
“…These facts further emphasize the importance of external jugular vein cut down procedure which uses tunneled catheter with larger lumen diameter and has negligible rate of misplacement if correctly measured and cut to size. [32][33][34][35][36][37] Catheter tips can change position on moving from lying to standing. Most insertions are done in a supine or head down position.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Malposition can trigger arrhythmias either during or after insertion. [28,29] Rarely malposition causes cardiac tamponade, which may be fatal. [30] In our study, it was observed that non-infectious complications were less in lower extremity veins as compared with the upper extremity veins [ Table 4] and this difference was significant (P = 0.03).…”
Section: Discussionmentioning
confidence: 99%